Causes of hypoglycemia - Tywanek, Ewa; Trojanowska, Paulina; Woźniak, Magdalena; Wronecki, Jakub; Zwolak, Agnieszka; Łuczyk, Robert Jan (Journal of Education, Health and Sport, 2019)
Introduction: Hypoglycemia is metabolic state of ogranism characterized by abnormally low blood glucose level. Due to International Hypoglycemia Study Group (2017) and following Polish Diabetes Association Guidelines is is recognized with serum glucose below 70mg/dl – with or without accompanying symptoms, such as tremor or altered mental status or even hypoglycemic coma. Symptoms mentioned above may have huge impact on personal or social functioning of the patient. Purpose: To present a list of known causes of hypoglycemic state. Summary: Hypoglycemia is quite unpleasant and dangerous metabolic state that may be caused by multiple etiological factors. The most common cause of this condition is useing too much insulin in treatment of diabetes mellitus. Other diabetic drugs, such us for example sulphonylureas may result in hypoglycemia. Chemicals containing sulfhydryl group in their structure may result in severe hypoglycemia in progress of Insulin Autoimmune Syndrome (IAS). Organic basis of hypoglycemia due to increased amount of producing insulin may be recognized, in progress of pancreatic secreting tumor, called insulinoma. From the other hand functional abnormality of carbohydrate metabolism may be found. It’s called functional hypoglycemia and may develop due to presence of hyperinsulism and insulin resistance secondary to incorrect lifestyle and diet. Partly organic and functional cause of hypogycemia may be recognized after bariatric surgery. Fairy seldom hypoglycemia with low blood insulin level may be found. The example of this state constitutes Dodge-Potter Syndrome, when tumor is able to produce insulin-growth factor 2 (IGF-2) stimulating insulin receptor, what results in serum glucose reduction. Hypoglycemia, as very adverse state for human organism, should be closely diagnose and efficiently treated.